Global rangelands with country boundaries - Getahun, Yasin; Flintan, Fiona E. (International Livestock Research Institute, 2018)
This map shows rangelands globally per country based on categorization of all 867 ecoregions in the TEOW(Terrestrial Ecosystems of the World) using the definitions of rangeland ecotypes and non-rangeland ecotypes, providing approximate areas of rangelands per country. This map classifies rangelands into four rangeland ecotypes (grasslands, shrublands, savanna/woodland, and tundra) and combines non-rangeland ecotypes into one 'other' layer. Rangeland types and boundaries were previously mapped by University of Idaho and the Society for Rangeland Management (SRM). Country boundaries were taken from ESRI 2016.